How stable are corporate capital structures? International evidence - He, Wen; Hu, Maggie Rong; Mi, Lin; Yu, Jin (Journal of Banking & Finance, 2021)
Using a large sample of firms from 43 markets, we find significant time-series variation in firms’ leverage ratios around the world. Industry median leverage ratios and aggregate leverage ratios also change substantially over time. Relative to actual leverage ratios, target leverage ratios estimated from the time-varying target models are much more stable. Variance decomposition shows that leverage instability is largely driven by deviations from the target. A number of firm and market characteristics are related to capital structure instability. We also find evidence consistent with firms using financing activities to adjust their leverage ratios towards the target in global markets.